New Pathogenic and Therapeutic Concepts in Systemic Sclerosis - Hügle, Thomas; Huigens, Christiaan A.; van Laar, Jacob M. (Arzneimittelforschung, 2009)
Systemic sclerosis (SSc) is an autoimmune disease of unknown origin. The clinical hallmarks are progressive fibrosis of skin and internal organs and vasculo-pathic changes in the form of digital ulcers and pulmonary arterial hypertension. The chronicity and heterogeneity of the disease has hampered research in SSc in the past, but new research tools and animal models have contributed to a greater understanding of the pathogenesis of SSc and resulted in new findings in the fields of genomics, cytokine expression, autoantibodies and abnormalities of blood progenitor or effector cells. As a consequence, targeted therapeutic compounds such as imatinib are currently under clinical investigation. Whilst the search for an effective “targeted therapy” is still ongoing, autologous stem cell transplantation represents a “multi-target” approach aiming at “resetting” the immune system. This review gives an overview of the translation from pathogenic findings into therapeutical application.
Keywords: Fibrosis; Pathogenesis; Scleroderma; Stem cell transplantation; Systemic sclerosis; Therapy, cellular, targeted